The family in Central Asia: new perspectives - Roche, Sophie (Islamkundliche Untersuchungen, 2020)
Frontmatter -- Table of contents -- The Family in Central Asia: New Research Perspectives -- The Paradox in Studies of Family in Central Asia -- Mahalla in Northern Tajikistan -- The Family in the Kolkhoz Context -- The Family in the Kolkhoz Context An Approach to the Apparently Contradictory Relationship between Modernity and Tradition in the Brezhnev Era -- Marriage Strategy in the Aftermath of the Conflict in Osh, Kyrgyzstan -- “Better to hold on to salt than to hold on to your daughter” Marriage Strategy in the Aftermath of the Conflict in Osh, Kyrgyzstan -- Impacts of the 1978 Communist coup d’état -- Tajik in Content—Soviet in Form? -- The Sacred Families in Central Asia -- Kelin in Central Asia -- The Role of Women in Health-Seeking Strategies -- Historical Analysis of the Family and the Education of Children -- Global Familyhood and Global Family Communication: Cases from Afghanistan -- Kinship and Orphans: Rural Uzbeks and Loss of Parents in the 1920s and 1930s -- A Family Affair. Sibling Hierarchy, Moral Reasoning, and Differential (Im)mobility in Rural Kyrgyzstan -- A Network Analysis of Qipchaks in Mongol China -- Towards Matrifocal Families? Relations in Transnational and Single Parent Families in Tajikistan -- Anthropological Genetics in Central Asia -- Population Change and Migration in the Ferghana Region -- Ethnographic Sketches in “The Mineralogy” of Abu-Rayhon Biruni -- Film Review Nurbek Egen: The Empty Home (Pustoi dom), 2012 -- Glossary: Family terminology -- Bibliography